Causal linkages between stock, crude oil and gold returns in Central Europe - Mamcarz, Katarzyna (Publishing House of Wroclaw University of Economics and Business, 2024)
The aim of this paper was to evaluate the relationship between the stocks, crude oil and gold markets of Central Europe in the short and long-term by applying a vector error correction model (VECM), and the Granger-causality analysis followed by a forecast error variance decomposition (FEVD) and impulse response function (IRF) analysis. Since gold seems to demonstrate a low or negative correlation with stocks, while the correlation between crude oil and gold is positive, it is important to investigate the interrelations in the markets in question to understand the nature of the linkages between them and their implications. It is assumed that there exists a long-term equilibrium between the analysed assets and that the changes in the prices in the gold and crude oil markets impact the stock market. The research findings confirm a long-term relationship between the markets as the prices of the analysed assets are cointegrated. In the long-term, the increase in the crude oil price (Brent) caused a raise in the gold price, whereas the impact of the stock price (Central European Blue Chip Index CETOP) was opposite. The author indicated two cases of unidirectional causality, hence the gold returns Granger-cause the stock returns, as expected. However, the latter determined the crude oil returns, which contradicts the research hypothesis. One can observe the negative impact of gold returns on the stock returns, whilst the stock returns have a positive impact on the crude oil returns. To the best of the author’s knowledge, no similar research with the use of VECM was devoted to the interrelations between the stock, crude oil and gold markets of Central Europe described in this paper. Most of the research focused on countries classified as the key producers and consumers of gold.
Argumenta Oeconomica, 2024, Nr 2 (53), s. 66-89
Keywords: capital investments; stock; crude oil; gold; Granger causality